Clinical application of neostigmine in antagonizing postoperative residual curarization after elective laparoscopic gastrointestinal surgery - CHEN Qiufen; CHEN Qiufen; MIN Su; YU Chang; LYU Feng; ZHANG Yuxi (陆军军医大学学报, 2023)
Objective To investigate the clinical effects of the timing and dosage of neostigmine on its antagonistic effects on postoperative residual curarization (PORC) induced by rocuronium in patients undergoing laparoscopic gastrointestinal surgery during recovery of general anesthesia. Methods A total 220 patients undergoing elective laparoscopic gastrointestinal surgery in the First Affiliated Hospital of Chongqing Medical University from November 2021 to February 2022 were recruited in this study. They were randomly divided into 4 groups, with 55 patients in each group. After spontaneous muscle relaxation recovery to train-of-four count (TOFC)=1, the patients in groups A1 and A2 were intravenously given 0.04 mg/kg neostigmine +0.02 mg/kg atropine and 0.06 mg/kg neostigmine combined with 0.03 mg/kg atropine, respectively. In contrast, after spontaneous muscle relaxation recovery instead to train-of-four ratio (TOFr, T4/T1)=0.4, the patients in groups B1 and B2 were intravenously given 0.04 mg/kg neostigmine +0.02 mg/kg atropine and 0.06 mg/kg neostigmine +0.03 mg/kg atropine, respectively. The physical and physiological characteristics of the patients before operation, and the physiological parameters, medication, operation, anesthesia, bleeding volume, awakening and sedation of the patients during operation were recorded and analyzed comparatively. Hemodynamic changes before and after the administration of neostigmine were monitored and recorded. The durations from the last administration of muscle relaxant to different stages of muscle relaxation recovery, defined by the values of TOFC=1, TOFC=3, TOFr=0.4, TOFr=0.7 and TOFr=1.0, were analyzed comparatively. The changes in TOFr after extubation were also analyzed comparatively. Results Eighteen patients were excluded from the trial, and, consequently, 202 patients were finally enrolled. The A1, A2, B1 and B2 groups took 94.53 (95%CI: 92.84~96.23), 85.88 (95%CI: 84.91~86.86), 75.08 (95%CI: 72.95~77.20) and 68.30 min (95%CI: 66.53~70.07), respectively, to recover to TOFr=1.0 from the last administration of rocuronium bromide, and significant difference was seen in recovery time among the 4 groups (all P < 0.05). In every group except B2, there was at least 1 patient suffering from PORC, with an incidence of 14.29% (95%CI: 5.94%~27.24%), 7.84% (95%CI: 2.18%~18.88%) and 1.92% (95%CI: 0.05%~10.26%), respectively in the other 3 groups in turn, which was significantly different from that in B2 group (P < 0.05). Conclusion For patients undergoing laparoscopic gastrointestinal surgery during recovery of general anesthesia, administration of 0.06 mg/kg neostigmine+0.03 mg/kg atropine when TOFr=0.4 can accelerate the recovery of muscle tone and reduce the incidence of PORC after extubation.